Foliar Treatments with Urea and Nano-Urea Modify the Nitrogen Profile of Monastrell Grapes and Wines - María José Giménez-Bañón; Juan Daniel Moreno-Olivares; Juan Antonio Bleda-Sánchez; José Cayetano Gómez-Martínez; Ana Cebrián-Pérez; Belén Parra-Torrejón; Gloria Belén Ramírez-Rodríguez; José Manuel Delgado-López; Rocío Gil-Muñoz (Horticulturae)
Foliar application of nitrogen can increase readily assimilable nitrogen in grapes without increasing vegetative growth and yield. Recently, nano-formulations have been used to achieve a controlled and precise release of agrochemicals, avoiding losses due to degradation and volatilisation that could cause environmental problems. In this study, foliar urea treatments were applied to Monastrell grapevines in two different formats during three consecutive seasons. The treatments were administered at veraison and one week later, consisting of control, urea, and calcium phosphate nanoparticles doped with urea. The amino acids and ammonium contents were subsequently quantified in both grapes and resulting wines by HPLC-DAD. The results in the grapes depended on the season: in 2019, both treatments produced an increase in total nitrogen content; in 2020, only the nano-treatment caused it; in 2021, both treatments incremented nitrogen content. With regard to the effect on the wines, the results also depended on the season. Thus, in 2019 and 2020, there were increases in nitrogen content in the wines from the nano-treatments, in contrast to 2021 where the increase was in the urea treatment. In conclusion, both treatments can be used to prevent nitrogen deficiency in grapes and guarantee adequate fermentation development, with the additional economic and environmental advantages of nano-treatment due to the lower dosage.